Crop seed oil bodies: From challenges in protein identification to an emerging picture of the oil body proteome. Issue 12 (6th June 2013) - Jolivet, Pascale; Acevedo, Francisca; Boulard, Céline; d'Andréa, Sabine; Faure, Jean‐Denis; Kohli, Ajay; Nesi, Nathalie; Valot, Benoit; Chardot, Thierry
Abstract : Oleaginous seeds store lipids in specialized structures called oil bodies (OBs). These organelles consist of a core of neutral lipids bound by proteins embedded in a phospholipid monolayer. OB proteins are well conserved in plants and have long been grouped into only two categories: structural proteins or enzymes. Recent work, however, which identified other classes of proteins associated with OBs, clearly shows that this classification is obsolete. Proteomics‐mediated OB protein identification is facilitated in plants for which the genome is sequenced and annotated. However, it is not clear whether this knowledge can be dependably transposed to less well‐characterized plants, including the well‐established commercial sources of seed oil as well as the many others being proposed as novel sources for biodiesel, especially in Africa and Asia. Toward an update of the current data available on OB proteins this review discusses (i) the specific difficulties for proteomic studies of organelles; (ii) a 2012 census of the proteins found in seed OBs from various crops; (iii) the oleosin composition of OBs and their role in organelle stability; (iv) PTM of OB proteins as an emerging field of investigation; and finally we describe the emerging model of the OB proteome from oilseed crops.